Hirsutism - Evaluation and Treatment (Delta Medical College Journal, 2016)
Hirsutism is a distressing clinical condition seen in adult female patients. The cause is mainly hyperandrogenism, which may be ovarian or adrenal. The most common pathological cause is usually polycystic ovary syndrome. It may be part of a rare metabolic syndrome, drug induced, or just idiopathic. It requires in depth clinical evaluation and investigation for treatment. Serum testosterone measurements are not needed in many cases. Hirsutism has a huge psychosocial impact, especially in the young females. This article reviews the current evaluation guidelines and management of hirsutism.Delta Med Col J. Jan 2016 4(1): 35-44